Eficacia del adelantamiento de la barrera de protección en las infracciones de tránsito en la ciudad de Ibarra en el año 2022 - Páez Pazmiño, Nicole Gabriela (2024)
The present study focused on investigating the effectiveness of overtaking the protection barrier in traffic violations in Ibarra during the year 2022. With the general objective of analyzing the application and effectiveness of the legal principle in cases of driving while intoxicated and excessive. of speed. The methodology used was a mixed approach, quantitative for the analysis of numerical data of infractions and accidents validating the influence of overtaking the protective barrier and qualitative for the analysis of the relevant documentation and description of the cases of intoxication. and speeding. As a research method, the normativist method was applied, which allowed us to investigate the different regulations related to the study topic. Therefore, the technique used was a documentary review of jurisprudence, since the cases that have judicial rulings registered in the Provincial Unit of Jurimetric Studies and Statistics were investigated, developing the instrument of the observational record in which it is described in detail. the main characteristics for the identification of processes related to the advancement of protection barriers. 8 cases of drunkenness and 11 of speeding were analyzed in Ibarra in 2022\; sampling was not carried out due to the elimination of radars. In this way, the judicial cases and legal provisions of the Comprehensive Organic Penal Code are analyzed. The results reflected the correlation between the consistent application and application of protective barriers and the reduction of road incidents. In conclusion, the importance of implementing clear protocols and training to strengthen the understanding and effective application of the legal framework is highlighted. It is recommended to establish a continuous monitoring system to evaluate the effectiveness of the established protection mechanisms.